KEEFEKTIFAN MODEL EXPERIENTIAL LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR IPA - Zuhryzal, Afief; Fatimah, Mur (Indonesian Journal of Conservation, 2019)
This study aims to determine the effectiveness of Experiential Learning model on science learning in grade V of SD Debong Kidul Tegal City. Experimental design used was Quasi Experimental in the form of nonequivalent control group design. The result of hypothesis testing of effectiveness Experiential Learning model to nautral science learning motivation showed that thitung > ttabel (3,882 ≥ 2,037)and the result of learning showed that thitung> ttabel (5,269 ≥ 2,037). It can be concluded that the implementation of Experiential Learning model is effective on the motivation and learning outcomes of science students of grade V on the subject.